2021
DOI: 10.3390/su131810259
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Hydrological-Hydraulic Modeling of Urban Floods Using InfoWorks ICM

Abstract: Malaysia, being a tropical country located near the equatorial doldrums, experiences the annual occurrence of flood hazards due to monsoon rainfalls and urban development. In recent years, environmental policies in the country have shifted towards sustainable flood risk management. As part of the development of flood forecasting and warning systems, this study presented the urban flood simulation using InfoWorks ICM hydrological−hydraulic modeling of the Damansara catchment as a case study. The response of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The comparison of the observed and modeled water level time series is shown in Figure 4. The previous results from another proprietary software, InfoWorks Integrated Catchment Modeling (ICM) [43], are also presented for comparison purposes in the same plot. In Figure 4, the overall water profiles match well with the observation for both the calibration and validation periods.…”
Section: One-dimensional River Flow Modelingmentioning
confidence: 99%
“…The comparison of the observed and modeled water level time series is shown in Figure 4. The previous results from another proprietary software, InfoWorks Integrated Catchment Modeling (ICM) [43], are also presented for comparison purposes in the same plot. In Figure 4, the overall water profiles match well with the observation for both the calibration and validation periods.…”
Section: One-dimensional River Flow Modelingmentioning
confidence: 99%
“…Then they used MIKE FLOOD coupling to simulate the inundation extents and depths of the study area under different grades of flood. Sidek et al used the InfoWorks ICM to construct a 1D river and 2D surface inundation coupling model in the Damansara catchment, Malaysia [ 28 ]. The model was verified by monitoring data, and the results showed that the model has a good accuracy (R 2 > 0.8).…”
Section: Introductionmentioning
confidence: 99%
“…The municipal infrastructure needs to update with appropriate flood management (Wang et al, 2008;Zhang et al, 2019), and since the capability of the sewerage system in the Zhengzhou metropolitan region is insufficient, further improvements are required. Wang et al (2021) utilized remoting sense images with high precision (Sidek et al, 2021) coupled with urban hydrological models (Chen et al, 2021) to evaluate the possibility of potential flood hazards, and Wu et al (2021) represented the correlation between social indicators (such as population) and direct economic losses. Furthermore, Lv, Meng, et al (2021) introduced the Flood Inundated Depth-Loss Rate Function (FILF), accompanied by images of land-use classification and the Digital Elevation Model (DEM) to estimate the losses caused by extreme precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Ogden et al (2011) revealed the correlation between surface floods and drainage discharges in extreme precipitation, and they showed that changes in imperviousness could significantly affect flood peaks. Sidek et al (2021) Other approaches to estimating drainage capability include numerical simulation (Lv, Wang, et al, 2021) and physical experiments (Naves et al, 2020) using a hydrodynamic model, which presented the conversion process from precipitation in the watershed to the drainage network (Martínez et al, 2021). Imk et al (2021) Researchers introduced a new methodology combining hydrodynamics with hydrological models to simulate water transportation from the surface to drainage pipes and obtained the relationship between precipitation and metropolitan submergence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation